The scarecrow a novel - Connelly, Michael 1956- (Little, Brown and Co. Large Print, 2009)
Newspaperman Jack McEvoy decides to use his final days at the LA Times to write the definitive murder story of his career. Focusing on the case of Alonzo Winslow, a 16-year-old drug dealer in jail after confessing to a brutal murder, Jack realizes that Winslow's so-called confession is bogus and that the real killer is operating completely below police radar--and with perfect knowledge of any move against him.